SCIENTIFIC AND THEORETICAL FOUNDATIONS OF INNOVATIVE MANAGEMENT OF THE GREEN ECONOMY - Maksudova Shaxzoda (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The green economy represents a paradigm shift in economic development, emphasizing sustainability, environmental responsibility, and social equity. This article explores the scientific and theoretical underpinnings of innovative management in the green economy, highlighting the interdisciplinary foundations, key concepts, and strategic approaches necessary for effective implementation. It discusses the integration of innovation, sustainability science, and systems thinking to drive transformative change in economic practices.